Students’ perceptions of the accounting department on the factors affecting accountants’ ethical behavior - Hidayati, Umi Rizeki; Nor, Wahyudin; Safrida, Lili (Journal of Contemporary Accounting, 2022)
This study was conducted to examine and analyze the influence of academic self-efficacy, fraud diamond, knowledge level, Machiavellian, and love of money on accountants’ ethical behavior. Research respondents were students of the Accounting Department University of Lambung Mangkurat Banjarmasin; Sekolah Tinggi Ilmu Ekonomi Indonesia Banjarmasin (STIEI) Banjarmasin; National College of Economics (STIENAS) Banjarmasin; and Pancasetia College of Economics (STIEPAN) Banjarmasin. The data were processed using multiple linear regression analysis with classical assumption test. The results of the research prove that academic self-efficacy and level of knowledge have a significant negative effect on the ethical behavior of accountants. Meanwhile, fraud diamond and machiavellian have an insignificant positive effect on the ethical behavior of accountants, and love of money has a significant positive effect on the ethical behavior of accountants.